Economic Valuation of Forest Goods and Services of Ayer Hitam Forest, Puchong, Selangor - Abd. Ghani, Awang Noor; Othman, Mohd Shahwahid; Yacob, Mohd Rusli; Mohamed, Shukri; Hussin, Mohamed Zakaria (Universiti Putra Malaysia Press, 1999)
The conversion of forestland to other land uses has resulted in substantial loss of biodiversity and other potential economic values to the community. However, the potential economic values of forest resources have been largely ignored by policy makers and land use planners. An economic valuation of forest resources of Ayer Hitam Forest (AHFR), Puchong, Selangor was carried out to determine its economic value and its impact on land use changes. The study focused on valuation of timber resources, recreation, community roles and wildlife conservation. The results show that the economic value ofAHFR is substantial and ignoring this value in land use development would provide a wrong signal to policy makers. Future land use planning should consider not only market-based economic returns but also its non-market and other environmental benefits.